2023
DOI: 10.1007/s00024-023-03286-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distributions of b Values Following the 2019 Mw 7.1 Ridgecrest, California, Earthquake Sequence

Abstract: b value proposed in the Gutenberg-Richter (GR) law is one of fundamental physical parameters in statistical seismology, which has widely been applied in earthquake prediction, regional stress analysis and earthquake physics. Following the 2019 Mw 7.1 Ridgecrest earthquake sequence, a large number of aftershocks have been observed along the earthquake faults and available publicly. We conducted aftershock decaying analysis of these datasets based on the GR law for the spatiotemporal b values within the fault zo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In our study, we can observe that the M w 7.1 event occurs in the area where the parameter q M is increased. The spatiotemporal q M value distributions, based on the F-A model for each month after the mainshock of M w 7.1 can further be compared with the study by [52], in which the aftershock sequence is investigated in terms of the spatiotemporal b value distributions within the three-dimensional fault zone. The findings indicate that b values were initially homogeneous throughout the spatial area, with a low level of b value immediately following the mainshock.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we can observe that the M w 7.1 event occurs in the area where the parameter q M is increased. The spatiotemporal q M value distributions, based on the F-A model for each month after the mainshock of M w 7.1 can further be compared with the study by [52], in which the aftershock sequence is investigated in terms of the spatiotemporal b value distributions within the three-dimensional fault zone. The findings indicate that b values were initially homogeneous throughout the spatial area, with a low level of b value immediately following the mainshock.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a systematic study of the b-value parameter in New Zealand, reported by Smith (1981) [29], showed that within the vicinity of forthcoming large earthquakes there was firstly an increase in b-value and then a return to the initial value. Other important results on precursory changes in the frequency-magnitude b-value can be found in the literature [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 89%